New guidelines for hypertension in Russia - a priority of combined treatment - Yuriy Aleksandrovich Karpov; Yu A Karpov (Терапевтический архив, 2012)
This review provides an analysis of the results of Russian and foreign clinical trials that have shown a high antihypertensive efficacy and tolerability of combined medications containing fixed doses of perindopril and indapamide.